Identifikasi Masalah Kesehatan Masyarakat: Sebuah Study Cross Sectional - Kodriati, Nurul; Ningsih, Yesika Adi; Wuryandani, Riska Kirana; Arum, Amanda Sekar; Purnama, Rina; Fitria, Nafila Desca; Addabani, Azra Zein (STIKes Surya Global Yogyakarta, 2024)
Background of Study: Public health issues in Indonesia are still an important concern for policy makers and health workers. Low public awareness is one of the causes of not achieving a high degree of public health. This study aims to determine the description of the public health situation in Pringgolayan Village, Yogyakarta. Methods: This type of research is descriptive quantitative with a population of all heads of families registered in Pringgolayan Hamlet totaling 117 heads of families. Sample calculation using the formula and obtained 100 samples. The sampling technique used was purposive sampling. Data collection time was conducted on February 10-17, 2023 in Pringgolayan, Yogyakarta. The data that has been obtained is by conducting interviews on several question indicators consisting of infectious diseases, non-communicable diseases, occupational health and safety, availability of family medicinal plants (TOGA), drinking water facilities, clean and healthy living behavior (PHBS), and history of mental disorders. Interviews were conducted with family representatives by visiting from house to house in Pringgolayan. Results: The identification of public health problems is described through 5 indicators, namely infectious diseases, non-communicable diseases, occupational health and safety in households, TOGA plants and drinking water facilities, clean and healthy living behaviors and mental disorders. Each indicator has a category whose assessment is based on the behavior and actual conditions of the Pringgolayan community. Conclusion: There are five indicators that become health problems, namely hypertension, diarrhea, not using tools to move heavy loads, and not having TOGA plants. Keywords: Health Problems, Community, Disease.